Constructing images of HCWs in Chinese government Weibo posts: a discourse-historical approach - Wang, Xueyu; Zheng, Zheng (Frontiers in Communication, 2024)
This study examines the image construction of front-line healthcare workers (HCWs) in Chinese government Weibo (microblogs) during the COVID-19 pandemic. Specifically, we rely on a discourse-historical approach to analyze 1,510 posts collected from an influential government Weibo account, @healthchina (健康中国), during the first wave of the pandemic to investigate the diverse images of HCWs constructed, the discursive strategies employed, and the pragma-linguistic devices used by @healthchina. The data analyses find that Chinese HCWs are depicted as professional and competent in addressing the pandemic crisis, compassionate and caring to their patients, and responsible and devoted to public health. Two discursive strategies are found salient in HCW's image construction-nomination and predication realized through the identity labels, attitude/judgment resources, metaphors and comparisons, pictures, and hashtags. We argue that Chinese government microbloggers intentionally constructed these images of the HCWs to elicit positive emotional responses, reinforce government trustworthiness, and foster social cohesion in the collective fight against the pandemic. This research underscores the strategic communication efforts aimed at shaping the perception of HCWs and their pivotal role in managing the pandemic.